Computer-based interventions to improve self-management in adults with type 2 diabetes: a systematic review and meta-analysis. - Pal, K; Eastwood, S; Michie, S; Farmer, A; Barnard, M; Peacock, R; Wood, B; Edwards, P; Murray, E (American Diabetes Association Inc., 2014)
OBJECTIVE: Structured patient education programs can reduce the risk of diabetes-related complications. However, people appear to have difficulties attending face-to-face education and alternatives are needed. This review looked at the impact of computer-based diabetes self-management interventions on health status, cardiovascular risk factors, and quality of life of adults with type 2 diabetes. RESEARCH DESIGN AND METHODS: We searched The Cochrane Library, Medline, Embase, PsycINFO, Web of Science, and CINAHL for relevant trials from inception to November 2011. Reference lists from relevant published studies were screened and authors contacted for further information when required. Two authors independently extracted relevant data using standard data extraction templates. RESULTS: Sixteen randomized controlled trials with 3,578 participants met the inclusion criteria. Interventions were delivered via clinics, the Internet, and mobile phones. Computer-based diabetes self-management interventions appear to have small benefits on glycemic control: the pooled effect on HbA1c was -0.2% (-2.3 mmol/mol [95% CI -0.4 to -0.1%]). A subgroup analysis on mobile phone-based interventions showed a larger effect: the pooled effect on HbA1c from three studies was -0.50% (-5.46 mmol/mol [95% CI -0.7 to -0.3%]). There was no evidence of improvement in depression, quality of life, blood pressure, serum lipids, or weight. There was no evidence of significant adverse effects. CONCLUSIONS: Computer-based diabetes self-management interventions to manage type 2 diabetes appear to have a small beneficial effect on blood glucose control, and this effect was larger in the mobile phone subgroup. There was no evidence of benefit for other biological, cognitive, behavioral, or emotional outcomes.